The effects and time lags of R&D spillovers in Brazil. (November 2016) - Moralles, Herick Fernando; do Nascimento Rebelatto, Daisy Aparecida
Abstract: Government's innovation investments for science intensive sectors, such as the capital goods industry for developing countries play an important role in technology dissemination; however, few studies have addressed this issue. This study is conducted in the framework of a developing economy (Brazil), and aims to estimate the spillover effects throughout the industry resulting from public investment in innovation, as well as the spillovers of R&D and management investment performed by the capital goods industry through the rest of the industrial sector, and also the time lapse between the occurrence of innovative investment and output growth due to such expenditures. The results of the estimated econometric model exhibit significant and positive spillover effects by the government R&D expenditures for the capital goods industry with a three-year lapse, as well as a one-year lag for the occurrence of output effects on the other companies of the manufacturing sector, resulting from innovative investments by the capital goods industry. Highlights: We calculate the spillover from public and capital goods investments in innovation. We measure the time lapse between the innovative investments and output growth. The two alternative econometric models were used to calculate the spillover effects. It's a three-year lag for the manufacturing sector absorbs innovative public investments. Capital goods sector is faster than the rest of industry to uptake innovative spillovers